Selection for fertility in lactating dairy cows: implications of conceptus-derived signals - Liebig, Bethany Ellen, author; Hansen, Thomas R., advisor; Thomas, Milton G., committee member; Van Campen, Hana, committee member; McConnel, Craig S., committee member (Colorado State University. Libraries, 2016)
Infertility is a source of major economic loss in the dairy industry. Selection for fertility in dairy cows is difficult because fertility traits based on a genetic evaluation, such as daughter pregnancy rate (DPR), are lowly heritable (h2 ≤ 0.04), influenced by on-farm events, such as services per conception (SPC), and influenced by complex mechanisms that cause embryo mortality (EM). Embryo survival depends on robust interferon tau (IFNT) production and release from the trophectoderm, induction of IFN stimulated genes (ISG) in the endometrium to block the luteolytic, pulsatile release of prostaglandin F2α (PGF), and continued progesterone production by the corpus luteum throughout maternal recognition of pregnancy. Genes negatively affecting IFNT and ISG expression may increase the occurrence of EM. We hypothesized that selection for high direct genomic value for DPR (DGV-DPR) and low on-farm SPC records would be associated with increased: 1) IFNT production by the conceptus, 2) ISG expression in endometrium and peripheral blood mononuclear cells (PBMC), and 3) embryo survival. Freshening dairy cows (n=86) were sorted by DGV-DPR (determined by Clarifide®, Zoetis) and SPC into high fertile (HF; -1.3 DGV-DPR; 1.4 SPC) nonpregnant (NP) or pregnant (HP), and low fertile (LF; -2.3 DGV-DPR; 3.7 SPC) pregnant (LP) groups (n = 7 each). After the voluntary wait period, cows were estrous synchronized and time-artificially inseminated to a HF bull (+1.8 DPR). NP cows were not inseminated. On day 16 following onset of estrus, embryos were flushed from the uterus and typed as viable or EM based on morphology and length. The DGV-DPR was negatively correlated (r = -0.57; P < 0.05) with SPC. Days in milk and number of lactations were not different between groups. Serum progesterone tended (P < 0.10) to be lower in the cows carrying EM embryos than NP cows. Two of 7 embryos from HP cows and 3/6 embryos from LP cows were classified as EM. Viable embryos were significantly (P < 0.05) longer than EM embryos when fertility group was not considered. Viable HP embryos tended to be longer (P < 0.10) than LP embryos. Interferon tau concentrations in uterine flushing (UF) were: 1) greater in HP compared to LP and NP cows (P < 0.05), 2) positively correlated with DPR (r = 0.68; P < 0.05) and 3) negatively correlated with SPC (r = -0.59; P < 0.05). Interferon stimulated gene 15 mRNA concentrations were significantly: 1) upregulated in endometrium from HP viable compared to LP viable and NP cattle (P < 0.05), and 2) upregulated in peripheral blood mononuclear cells from HP compared to LP and NP cows (P < 0.05). Furthermore, ISG15 protein concentrations in endometrial tissue were significantly upregulated in HP compared to LP and NP cattle (P < 0.05). In conclusion, selection of dairy cows combining DPR and SPC may improve fertility through increased production and action of IFNT.
Keywords: conceptus; fertility; pregnancy; dairy; bovine; interferon tau